Neopterin levels and dexamethasone suppression test in obsessive-compulsive disorder - Kuloglu, Murat; Atmaca, Murad; Onal, Suleyman; Gecici, Omer; Bulut, Vedat; Tezcan, Ertan (Elsevier Ireland Ltd, 2007)
Neopterin, a biopterin precursor that is released by macrophages, is an important immunological marker in psychiatric disorders. It has been reported that glucocorticoids may cause suppression of cell-mediated immunity and consequently result in decreased neopterin levels. In the present study, we evaluated whether dexamethasone suppression test (DST) and neopterin findings were associated with pure obsessive-compulsive disorder (OCD) patients (OCD-D group) and the concomitant OCD and depression (OCD+D group). The sample comprised 44 patients with OCD (27 with OCD-D and 17 with OCD+D) and 30 control subjects. There was significantly higher DST nonsuppression in the OCD+D group than in the OCD-D group. With regard to mean neopterin levels, there was no significant difference between the OCD-D group and the control group, but there was a statistically significant difference between the OCD+D group and the control group. The OCD+D group had significantly lower neopterin levels than the 20 OCD-D group. We suggest that this distinction may reflect the fact that glucocorticoids can lead to suppression of cell-mediated immunity and consequently can result in decreased neopterin levels. In conclusion, our results suggest that not the OCD-D group had normal neopterin levels and DST results, and also that OCD may be a heterogeneous subtype characterized by some biological indicators or anxiety and affective disorders. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: OCD; neopterin; DST; depression